Determinants of high blood pressure and barriers to diagnosis and treatment in Dar es Salaam, Tanzania. Issue 12 (December 2016) - Zack, Rachel M.; Irema, Kahema; Kazonda, Patrick; Leyna, Germana H.; Liu, Enju; Spiegelman, Donna; Fawzi, Wafaie; Njelekela, Marina; Killewo, Japhet; Danaei, Goodarz
Abstract : Objectives: We assessed the prevalence and determinants of high blood pressure (BP), and barriers to diagnosis and treatment, in Dar es Salaam, Tanzania. Methods: We surveyed and screened 2174 community-dwelling adults aged at least 40 years in 2014 and conducted a follow-up after 1 year. Results: Median BP was 131/81 mmHg, and hypertension prevalence was 37%. Mean adjusted difference in SBP was 4.0 mmHg for overweight, 6.3 mmHg for obese class I, and 10.5 mmHg for obese class II/III compared with normal weight participants. Those who were physically inactive had 4.8 mmHg higher SBP compared with those with more than 24 h of moderate or vigorous activity per week. Drinkers of at least 10 g of alcohol per day had 4.5 mmHg higher SBP than did nondrinkers. Among hypertensive participants, 48% were previously diagnosed, 22% were treated, and 10% were controlled. Hypertensive participants without health insurance were 12% less likely to have been previously diagnosed than insured hypertensive participants. Of referred participants, 68% sought care, but only 27% were on treatment and 8% had controlled BP at follow-up. Reasons for not seeking care included lack of symptoms, cost of visit, and lack of time. Reasons for not being on treatment included lack of symptoms, not being prescribed treatment, and having finished one course of treatment. Conclusion: Major risk factors for hypertension in Dar es Salaam are overweight, obesity, inadequate physical activity, and limited access to quality medical care. Increased insurance coverage and community-based screening, along with quality medical care and patient education, may help control this burgeoning epidemic. Abstract : Supplemental Digital Content is available in the text